Application of Home Medication Review (HMR) on Patient Adherence in Type 2 Diabetes Mellitus (T2DM) Blood Sugar Management - Sari, Yelly Oktavia; Permatasari, Dita; Mariza, Wilnando; Fitria, Najmiatul; Lailiani, Resa (JSFK (Jurnal Sains Farmasi & Klinis), 2022)
Non-adherence of type 2 diabetes mellitus (T2DM) patients in treatment will impact expected clinical outcomes, risk of complications, and poor quality of life. Home medication review (HMR) is designed to help achieve optimal treatment, such as patient adherence. This study aimed to determine adherence levels and T2DM blood sugar management. This study with a pretest-posttest control group design was carried out at Andalas Public Health Center, Padang City, West Sumatra-Indonesia with 62 randomly selected respondents and then divided into two groups (pillbox and non-pillbox). The adherence levels were assessed by the pill count method. Changes in blood sugar levels are associated with adherence levels. The results showed an increase in the T2DM adherence level of patients using the pillbox at 7.360% and a decrease in blood sugar levels in those who used the pillbox at 61.161 mg/dL. There was a significant difference in the adherence between patients' levels using the pillbox and non-pillbox with a value of 0.011 (p <0.05). Similarly, the patient's blood sugar levels between the two groups showed a significant difference with a value of 0.007 (p<0.05). The application of HMR to patient adherence is considered to have a role in managing T2DM blood sugar.